Hubungan Power Otot Tungkai dengan Hasil Smash Bolavoli pada Pemain Usia 16-18 Tahun Jaya Vollyball Club (Jvc) Lubuklinggau - Sintia Sintia; Viktor Pandra; Yuli Febrianti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study investigates the relationship between leg muscle power and the effectiveness of volleyball smash performance among players aged 16–18 years at Jaya Volleyball Club (JVC) Lubuklinggau. Volleyball is a sport that requires a combination of physical strength, technical mastery, and tactical coordination, with the smash being one of the most decisive offensive techniques. The research was motivated by the observation that many junior athletes at JVC had not yet maximized their smash performance, particularly in terms of accuracy and power, which are strongly influenced by leg muscle explosiveness. The study employed a quantitative approach using purposive sampling with 35 participants selected from a population of 60 athletes. Leg muscle power was measured using the vertical jump test, while smash ability was assessed using a structured volleyball smash test. Data analysis was conducted with SPSS version 23, including descriptive statistics, normality tests using the Kolmogorov-Smirnov method, and Bivariate Correlation analysis (two-tailed). The results revealed a correlation coefficient (r) of 0.652, with a significance value of 0.000 (<0.05), indicating a statistically significant and strong relationship between leg muscle power and smash performance. These findings confirm that explosive power in the legs contributes greatly to the ability of young volleyball players to execute effective smashes. Athletes with higher vertical jump capacity tend to produce more accurate, powerful, and successful smashes, thereby increasing their contribution to team performance. The results emphasize the importance of integrating targeted leg muscle power training into volleyball coaching programs. Coaches and clubs are encouraged to design structured strength and plyometric training regimens to optimize players’ performance. Furthermore, this study provides valuable insights for athlete development programs and contributes to the broader understanding of physical conditioning in volleyball.